Statistical modelling and analysis of NCEA and New Zealand Scholarship assessment data - Johnston, Michael; Lillis, David (New Zealand Science Review, 2011)
​New Zealand’s main qualification system for senior secondary school comprises the three levels of the National Certificate of Educational Achievement (NCEA). These qualifications were introduced progressively, Level 1 first becoming available in 2002, Level 2 in 2003, and Level 3 in 2004. Additionally, the present system for awarding New Zealand Scholarship was first implemented in 2005. The NCEA system has several features that are quite unique, and that afford schools the opportunity to develop their own assessment programmes for a wide variety of courses in traditional, emerging, and cross-disciplinary subject areas. Those features of the NCEA system that afford this flex-ibility also present challenges from the psychometric point of view. In this paper, we describe a range of statistical modelling and analyses undertaken by the New Zealand Qualifications Authority (NZQA) to meet these challenges.